1993
DOI: 10.1103/physrevlett.71.2134
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the superconducting pairing state in YBCO from the phase coherence of YBCO-Pb dc SQUIDs

Abstract: We present an experiment designed to determine directly the symmetry of the pairing state in the cuprate superconductors.From the magnetic IIux modulation of YBCO-Pb dc SQUIDs, we determine the spatial anisotropy of the phase of the order parameter in single crystals of YBCO. The experimental results are complicated by SQUID asymmetries and the trapping of magnetic vortices, but taken as ã hole give rather strong evidence for a phase shift of n that is predicted for the d"2 y2 pairing state. This is further co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
632
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,087 publications
(659 citation statements)
references
References 16 publications
(8 reference statements)
25
632
1
1
Order By: Relevance
“…However, use of π-rings for a model spin system requires a large number of rings. The first superconducting π-rings, 8,9,10,11 which depended on the momentum dependence of the pairing wavefunction in the high-T c cuprate perovskite superconductors, were made using technologies which would be difficult to extend to many devices. Recently a technology that allows for photolithographic fabrication of π-shift devices and arrays of great complexity, using YBa 2 Cu 3 O 7−δ -AuNb (YBCO-Au-Nb) ramp-edge tunneling junctions has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of π-rings for a model spin system requires a large number of rings. The first superconducting π-rings, 8,9,10,11 which depended on the momentum dependence of the pairing wavefunction in the high-T c cuprate perovskite superconductors, were made using technologies which would be difficult to extend to many devices. Recently a technology that allows for photolithographic fabrication of π-shift devices and arrays of great complexity, using YBa 2 Cu 3 O 7−δ -AuNb (YBCO-Au-Nb) ramp-edge tunneling junctions has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…This state is characterised by an unusual vortex pattern in the form of a necklace of fractional vortices around the perimeter of the material, where neighbouring vortices have opposite current circulation. This vortex pattern is a result of a spectral rearrangement of current carrying states near the surfaces.The phase-sensitive experiments [1,2] carried out in the early 1990's showed that the high-temperature superconductors have predominantly d-wave pairing symmetry. Ever since, there has been an ongoing debate whether there exists a low-temperature phase that breaks time-reversal (T ) symmetry, in addition to the reflection symmetry of the crystal broken by the d-wave order parameter itself.…”
mentioning
confidence: 99%
“…3 We take the d x 2 −y 2 order parameter as having its positive lobe along the the crystalâ axis and its negative lobe along thê b-axis. 4 For symmetries obeyed by propagators and self energies, see 28 .…”
Section: A the Self-consistent Pinholementioning
confidence: 99%